2013
DOI: 10.1039/c3dt52135d
|View full text |Cite
|
Sign up to set email alerts
|

Selective one-pot syntheses of PtII–CuI heterobimetallic complexes of 4,5-diazafluorenide derivatives

Abstract: We report both the stepwise and one-pot syntheses of Pt(II)-Cu(I) hetero-dinuclear complexes using 4,5-diazafluorenide (L(-)) and 9-(2-(diphenylphosphino)ethyl)-4,5-diazafluorenide (L(p)(-)) as binucleating ligands. In the case of L(p)(-), the tethered phosphine arm helps anchor the Pt(II) centre onto the carbon site of the diazafluorenide and the Cu(I) centre is bound to the N,N-chelate site. In the case of L(-), the Cu(I) centre is bound to the carbon site of diazafluorenide and the Pt(II) centre is coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Along these lines, Song and co-workers have explored the coordination chemistry of daf and substituted diazafluorenes, including significant work aimed at leveraging this unique acid/base chemistry [15]. In their work, Song and co-workers have found that the acidic C-H bonds of daf can undergo deprotonation that results in follow-up reactivity [16][17][18][19][20]. More broadly, Stahl [21][22][23] and several other groups [24][25][26] have developed a number of catalyst systems supported by diazafluorene ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, Song and co-workers have explored the coordination chemistry of daf and substituted diazafluorenes, including significant work aimed at leveraging this unique acid/base chemistry [15]. In their work, Song and co-workers have found that the acidic C-H bonds of daf can undergo deprotonation that results in follow-up reactivity [16][17][18][19][20]. More broadly, Stahl [21][22][23] and several other groups [24][25][26] have developed a number of catalyst systems supported by diazafluorene ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of (NHC)M C X with compounds of other metals in the anionic species, negative charge of which is localized at the organic ligand, can be useful for the realization of path 2b [191]. The coordination at the coordination active site with the formation of bimetallic cationic species instead of transmetalation has been also observed using the chelate iridium cyclometalated [184] and ferrocene [192] structures in the presence of KPF 4 as source of the non-nucleophilic coordination anion.…”
Section: Reactions With the Formation Of Bimetallic Adducts Retaining The Nhc-m с Bondmentioning
confidence: 94%
“…26 Surprisingly when the metallation sequence is reversed and the [Cu(daf )(IPr)] complex is treated with [Pt(Ph) 2 (μ-SMe 2 ] n (n = 2 or 3), the exact same Pt(II)-Cu(I) heterobimetallic complex (as opposed to an isomer) was obtained. 26 In the process of generating [(IPr)Cu(daf )Pt(Ph) 2 ] from [Cu(daf )(IPr)] the {Cu(IPr)} + fragment was replaced by the {Pt(Ph) 2 } unit at the N,N-chelate site and migrated to the backbone C-donor. The built-in self-correction featured in the synthesis of the [(IPr)Cu(daf )Pt(Ph) 2 ] system allowed for a one pot synthesis to be successfully carried out (Scheme 4).…”
Section: Ii1 Coordination Chemistry Of the Parent Dafh And Daf − LImentioning
confidence: 99%
“…The synthesis of these Pt II -Cu I heterobimetallics is highly regioselective, and can also be performed in one-pot (Scheme 6). 26…”
mentioning
confidence: 99%